A study on factors that affect an employees’ job satisfaction in an organization / Maisarah Mohd Zulkiflee and Nurul Zayani Aziz - Mohd Zulkiflee, Maisarah; Aziz, Nurul Zayani (Faculty of Business and Management, 2014)
The study was conducted in order to find out the significant relationship between the independent variables with the dependent variable. The dependent variable is job satisfaction among employees in an organization. The independent variables in this study are pay and benefits and work environment. The results of the findings were interpreted using Reliability Test, Frequency Distribution, Descriptive Statistics and Pearson’s Correlation Coefficient. The population of the study referred to 285 employees in CTRM AC Sdn. Bhd. From the population, the sample size that had been selected is 164 employees in Value Stream 4 (VS 4) of Quality Control Department. This study sampling design is used probability sampling method which is simple random sampling as the sampling technique.